Unlocking Melawi Malay Medicine Mantras: Sound Patterns and Ecological Symbolism of Oral Literature - Putra, Ikhza Mahendra; Asfar, Dedy Ari; Syahrani, Agus (REiLA : Journal of Research and Innovation in Language, 2023)
The Melawi Malay community has a rich tradition of medicine using oral literature in the form of mantras, passed down through generations. These medicine mantras incorporate elements of beautiful sound and reflect the ecological, customary, and cultural values of the Malay people. This research aims to unveil the sound patterns and describe the symbolism of the triadic ecological elements, namely nature, nurture, and culture. To achieve this, purposive sampling was employed to select key informants, with Su Usnah, a traditional healer from Bina Karya, Melawi, being a crucial source. Through interviews and field notes, six relevant data sets were extracted from a pool of 15 available medicine mantras for analysis. Using a qualitative descriptive approach, this research utilized stylistic protocols to categorize the data according to existing sound patterns and employed ecocriticism guidelines to reveal the presence of ecological elements within the Melawi Malay medicine mantras. The primary findings of this research disclose the existence of four sound patterns in these mantras: assonance, alliteration, consonance, and rhyme. The ecocritical perspective reveals that each mantra contains ecological elements, including nature, such as flora and natural elements; nurture, reflecting the relationship between nature and society, and human connections; and culture, as manifested in customary practices. This study deepens our understanding of the sound patterns and ecological elements present in these mantras, with the hope that further research, through exploration of mantras in the Melawi Regency, can contribute to the continuous conservation and promotion of oral literature. Enriching the global understanding of mantras from linguistic, literary, and ecological perspectives is vital in practising traditional medicine in Melawi and other regions in West Kalimantan.